Mejoramiento de las competencias investigativas en los docentes no investigadores de la Universidad Laica Vicente Rocafuerte de Guayaquil - Menéndez Padrón, Adalberto (2016)
Taking into consideration the teaching experience and the empirical evidence identified by the authors in their work as educators at Universidad Laica VICENTE ROCAFUERTE de Guayaquil. Authors have identified gaps in the preparation of the professors who are not performing as educational researchers to implement formative research successfully in class with their students. This situation creates the following scientific problem: “How to improve the formation of research skills on professors who are not researchers at Universidad Laica VICENTE ROCAFUERTE de Guayaquil?” This gave rise to the present research project aimed at helping professors who do not perform as researchers in this university improve their research skills, as a way to enhance the research training of students. This paper is an approach to the results achieved up to date, namely a theoretical systematization that allowed the determination of a variable with its organization in dimensions and indicators for making the diagnosis to scientifically prove that empirical evidence that supports the need for the project and propose a solution.